'Winning Back Control': Migration, Borders and Visions of Political Community. (April 2021) - Schmidtke, Oliver
This article focuses on the governance of migration and borders as key issues of Brexit in a dual sense: as a contested political issue centrally fueling the Brexit debates and as an area of policy formation. First, the article addresses how Brexit has changed free movement as a key principle of the European integration project and transformed cross-border mobility between the European Union (EU) and the UK in a post-Brexit European border regime. Second, it discusses how the politicization of migration during the Brexit campaign has accentuated competing visions of political community. With a view to the effects of Brexit on the governance of migration and borders in Europe, the article demonstrates how the Brexit debates have emphasized the prominence of exclusionary nationalism, while they have simultaneously created new opportunities for the EU to launch a major reform of its migration and asylum policies.